Women and White-Collar-Crime : Debates on Gender, Fraud and the Corporate Economy in England and America, 1850-1930 - Robb, George (The British journal of criminology, 2006)
In Victorian society, women of the middle class were particularly vulnerable to white-collar crimes. Denied opportunities to earn their own living, single women were especially dependent on invested capital. Women, in fact, made up a significant portion of investors during the nineteenth century, especially in such key areas of the economy as banking, railways and insurance. Yet, bourgeois notions of gentility required that women remain ignorant of money matters and refrain from active participation in business affairs, leaving women especially exposed to all manner of fraud and malfeasance. This article uses financial literature, newspaper debates and popular fiction to demonstrate how women were victimized by white-collar crime. Women's financial victimization was a common theme of the popular press, economic journals and fiction. These discourses contributed to a feminist discourse of economic and political empowerment, and suffragists and other progressives argued that women had to reform an economy and financial system in which they were both marginalized and deeply implicated